MR1 deficiency enhances IL-17-mediated allergic contact dermatitis - Imahashi, Naoya; Satoh, Masashi; Clemente, Emanuela; Yoshino, Kazuhisa; Di Gioacchino, Mario; Iwabuchi, Kazuya (Frontiers in Immunology, 2023)
Major histocompatibility antigen complex (MHC) class Ib molecules are specific to a subset of T cells primarily involved in host defense against pathogenic microbes and influence the development of immune-mediated diseases. MHC-related protein 1 (MR1) is an MHC class Ib molecule that functions as a platform to select MR1-restricted T cells, including mucosal-associated invariant T (MAIT) cells in the thymus, and presents ligands to them in the periphery. MAIT cells constitute innate T-cell subsets that recognize microbial vitamin B2 metabolites and play a defensive role against microbes. In this study, we investigated the function of MR1 in allergic contact dermatitis (ACD) by examination of wild-type (WT) and MR1-deficient (MR1-/-) mice in which ACD was induced with 2,4-dinitrofluorobenzene (DNFB). MR1-/- mice exhibited exaggerated ACD lesions compared with WT mice. More neutrophils were recruited in the lesions in MR1-/- mice than in WT mice. WT mice had fewer MAIT cells following elicitation with DNFB, and MR1-/- mice lacking MAIT cells exhibited a significant increase in IL-17-producing alpha/beta and gamma/delta T cells in the skin. Collectively, ACD was severely induced in the MR1-/- background from an early phase with an enhanced type 3 immune response, although the precise mechanism of this enhancement remains elusive.